Fabrication of UV curable coating for super hydrophobic cotton fabrics. (18th February 2019) - Shen, Lixiang; Pan, Ya; Fu, Heqing
Abstract : A super hydrophobic cotton fabric was successfully prepared by a facile dip‐coating method using a synthetic fluorine‐free and UV curable super hydrophobic coating solution without additional particles. The obtained cotton fabric exhibited super hydrophobic property with a water contact angle above 159.5° and sliding angle 7.5°. Moreover, the treated cotton fabric could retain its super hydrophobic performance even after abrasion and accelerated laundering, as well as for different kinds of corrosive liquids. The coated cotton fabric was used to make up a surface tension‐driven, gravity‐assisted, floating oil–water separation device with separation efficiency above 99%. Additionally, the oil–water separation efficiency of super hydrophobic cotton fabric always was above 98% after 30 recycle times for cyclohexane–water mixture. POLYM. ENG. SCI., 59:E452–E459, 2019. © 2019 Society of Plastics Engineers